2013
DOI: 10.1007/s11010-013-1558-1
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde and 4-hydroxynonenal adducts are not formed on cardiac ryanodine receptor (RyR2) and sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA2) in diabetes

Abstract: Recently, we reported an elevated level of glucose-derived carbonyl adducts on cardiac ryanodine receptor (RyR2) and sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA2) in hearts of streptozotocin(STZ)-induced diabetic rats. We also showed these adduct impaired RyR2 and SERCA2 activities, and altered evoked Ca2+ transients. What is less clear is if lipid-derived malondialdehyde (MDA) and 4-hydroxy-2-nonenal (4-HNE) also chemically react with and impair RyR2 and SERCA2 activities in diabetes. This study used West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
(73 reference statements)
0
7
0
2
Order By: Relevance
“…Membranes were washed and incubated with horseradish peroxidase-conjugated mouse anti-rabbit IgG (Thermo, USA). Chemiluminescence detection was performed with the Amersham ECL detection kit according to manufacturer’s instructions ( Hofštetrová et al, 2010 ; Moore et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Membranes were washed and incubated with horseradish peroxidase-conjugated mouse anti-rabbit IgG (Thermo, USA). Chemiluminescence detection was performed with the Amersham ECL detection kit according to manufacturer’s instructions ( Hofštetrová et al, 2010 ; Moore et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…This finding supports the idea that altered activity of sarcolemmal NCX during Ca 2+ efflux contributes to the decrease in Ca 2+ transient-observed GK myocytes. Previous experiments in ventricular myocytes from the streptozotocin-induced diabetic rats have reported reduced caffeine-evoked Ca 2+ transients [ 82 91 ], SERCA2 activity, and Ca 2+ uptake [ 83 , 88 , 92 94 ] and decreased SR Ca 2+ channel (ryanodine receptor) activity [ 87 , 95 ] suggesting decreased SR Ca 2+ content, Ca 2+ uptake, and Ca 2+ release mechanisms in ventricular myocytes from the streptozotocin-induced diabetic rat.…”
Section: Intracellular Ca 2+ In Ventricular Myomentioning
confidence: 99%
“…The procedures used for these assays are detailed elsewhere [30, 43, 66]. We also began using adduct-specific antibodies to determine relative levels of MGO, GO, 4-HNE and MDA adducts on RyR2 and SERCA2a in hearts from control, diabetic and drug-treated diabetic animals [71], to gain insights into the role these RCS are playing in the pathophysiology of the disease.…”
Section: The Effects Of Mgo Go and 4-hne On Ryr2mentioning
confidence: 99%
“…The lack of immuno-reactive MDA and 4-HNE adducts were not due to the absence of RyR2 and SERCA2a proteins in our SR preparations, since these proteins were readily detected using RyR2 and SERCA2a antibodies (Figure7A and 7B, 5 th autoradiogram down). In a recent study, we showed that these antibodies detected MDA and 4-HNE adducts on proteins of M w between 30 kDa and 80 kDa in our SR preparation [71]. …”
Section: Amounts Of Mgo (Argpyrimidine) Go 4-hne and Mda Adducts Onmentioning
confidence: 99%